Authentication of Electronic Evidence; A Journey from Electronic Discovery to Digital Forensic Experts in Western Law-Recommendations for Pakistan - Hafsa Abbasi, Muhammad Asim Iqbal (JSSH, 2023)
This article claims that electronic evidence is not like physical evidence and requires some more guarantees of authentication which are not required otherwise. Electronic evidence needs some extra precautions to be taken care of during discovery and authentication procedures. Electronic discovery and authentication are inevitable procedures involved in electronic evidence trials, posing different challenges of electronic data and expert testimony therefore need to be ascertained from the perspective of Western as well as Pakistani law. Getting authentic and fool proof evidence to court is an important research question addressed by this research. Digital forensic experts are essential to carry on these procedures. Qualification of digital forensic expert is also important to be ascertained for seeking reliable evidence. Western laws are incorporating suitable laws and policies in order to cope up with the upcoming challenges of big data, management problems and preservation of ESI (electronically stored information). This research concludes that there is a need to upgrade laws and policies of Pakistan, which regulate authentication, discovery and expert testimony, as they are at very primitive stage